2013
DOI: 10.1007/s13105-013-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cardiac responses to alpha-lipoic acid in a rat-diabetic model: possible mechanisms?

Abstract: Alpha-lipoic acid (ALA) is widely used as an antioxidant for the treatment of diabetes and its complications; however, the pro-oxidant potential of ALA has recently been reported. This study was designed to investigate whether ALA supplementation could have pro-oxidant effects on cardiac tissues in normal and diabetic rats. Diabetes was induced by a single dose of streptozotocin (STZ; 55 mg/kg (intraperitoneal). Diabetic and normal rats were treated with ALA (100 mg kg(-1) day(-1)) for 45 days. ALA supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…On the other hand, there is connection with Cd exposure and diabetes as previous reports (4). Some research has demonstrated that the application of exogenous antioxidants can be supportive therapy to treat diabetes in mammals (11). In light of the above insight, the object of our study was to explore the potential influence of insulin and LA which is an antioxidant that has been clinically tested as a treatment for diabetes, against the Cd exposure in type I diabetic rats.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, there is connection with Cd exposure and diabetes as previous reports (4). Some research has demonstrated that the application of exogenous antioxidants can be supportive therapy to treat diabetes in mammals (11). In light of the above insight, the object of our study was to explore the potential influence of insulin and LA which is an antioxidant that has been clinically tested as a treatment for diabetes, against the Cd exposure in type I diabetic rats.…”
mentioning
confidence: 85%
“…Lipoic acid (LA), or 1,2-dithiolane-3-pentanoic acid, is a naturally consisting dithiol substance, essential for the functions as a cofactor for some mitochondrial enzymes, cause the manufacture of ATP. It is known that LA has strong antioxidant potency and is influential in both oxidative stress inhibition and management in a number of models or clinical conditions, including diabetes (11). LA is a powerful compound with amphipathic properties, is capable of extinguishing free radical, chelating metal and regenerating other antioxidants (6).…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of 250 µL of heart homogenate, 1.25 mL Trichloroacetic acid solution, and 0.5 mL thiobarbituric acid solution was heated for 30 min in a boiling water bath, cooled and centrifuged at 4°C, 3000 rpm for 10 min. The absorbance was measured at 535 nm against a reagent blank …”
Section: Methodsmentioning
confidence: 99%
“…Tissue processing [30] The hearts were excised and washed immediately with buffered saline (pH 7.4) to remove any red blood cells and clots. The tissues were then weighed and homogenized in normal saline (0.9%) for 2 min.…”
Section: Aerp Determinationmentioning
confidence: 99%
“…Histopathological analysis [30] Samples of heart tissues were washed immediately with saline (0.9%) and xed in 10% phosphate buffered formalin solution for 24 h. The tissues were then dehydrated in ascending grades of ethyl alcohol, cleared with xylene, and embedded in para n. Para n blocks were cut by a microtone to prepare 5 µm thick sections. Sections were stained with hematoxylin-eosin (H&E) to stain the nucleus and cytoplasm and with Masson's trichome to stain collagen bers for the detection of brosis.…”
Section: Detection Of Nox4 and Oxidative Stress-related Parametersmentioning
confidence: 99%